SCIDOT-14. ENHANCING BRAIN RETENTION OF A KIF11 INHIBITOR SIGNIFICANTLY IMPROVES ITS EFFICACY IN A MOUSE MODEL OF GLIOBLASTOMA - Gampa, Gautham (Neuro Oncol, 2019)
Glioblastoma, the most common and lethal of brain tumors, is both highly invasive and proliferative. This allows tumor cells to infiltrate into regions of the brain with an intact blood brain barrier and be protected from effective therapeutics. Thus, an ideal glioblastoma therapy needs to target cellular components that drive both invasion and proliferation, with inhibitors that penetrate the blood brain barrier. The mitotic kinesin KIF11 meets these criteria and it can be targeted with ispinesib, a highly specific small molecule inhibitor. However, to be effective, ispinesib needs to cross the blood brain barrier and be retained within brain long enough to target glioblastoma cells when they are vulnerable, during mitosis.. We have examined the factors that affect distribution of ispinesib to both brain and glioblastoma. We find that delivery of ispinesib is limited by P-gp and Bcrp-mediated drug efflux at the blood brain barrier. Consequently, ispinesib levels are significantly lower in the infiltrative tumor margin relative to the tumor core, where the blood brain barrier is defective. We also show that elacridar—an inhibitor of the P-gp and Brcp efflux transporters—enhances delivery of ispinesib, and that co-administration of ispinesib with elacridar markedly slows tumor proliferation and prolongs survival in a mouse model of this disease. These results demonstrate the feasibility and efficacy of combining a potentially ideal therapeutic with a compound that enhances brain retention of this therapeutic, and provides support for utilizing this approach in clinical investigations of KIF11 inhibitors in GBM.